Strategi Pengembangan Usaha Sapi Perah Skala Mikro Berwawasan Lingkungan di Kabupaten Subang, Jawa Barat - Petrus F.T.P. Tampubolon; Hermanto Siregar; Muladno -; M. Machfud (Institut Pertanian Bogor, 2011)
Until now, the development of the environmentally sound micro-scale dairy cattle business (USPSMWL) in the District of Sagalaherang and Ciater of the Subang Regency not fully reached the desired level yet. The growth of the dairy cow population of about 1% per year is still below the national growth of 1.29%; beside that, the environmental quality of some of the business of dairy cows (USP) is still not good yet. Results from the survey showed that most location of the cow shed was placed < 5 meters of residential houses. By the end of 2010, more than 80% dairy cow waste has not well managed, so it could be risk factors: air pollution,public health problem and odor. This study was intended to findstrategiesfor developing USPSMWL in Subang Regency. This study has used a method based on the analysis of Analytical Hierarchy Process (AHP). Respondents of this study were 6 experts, drawn from banking sector, animal husbandry sector, Dairy Milk Cooperative of Northen Bandung (KPSBU), Cooperative sector, Regency Government, and Environment sector.Theresults show that the “first priority actor” in the development USPSMWL in Subang Regency is “The Government of Regency, District, and Village ”; the “first priority factor” is “The readiness of the community”, the “first priority objective” is “The increasing community income”; and the “first priority strategy” is “The increasing readiness of the community/farmers to conduct the business of dairy farming (USP)”. Based on experts opinion in AHP, it can be concluded that the role of the Government of the Regency/District/Village in the development of USPSMWL in Subang Regency is the primary importance. The main strategy to be implemented is “to increase the community/farmers’ readiness to conduct dairy farming business (USP)”. It is matched with the real needs of communities in the location of the USP included (a) the need for increased knowledge and positive attitude of “non-dairy farmers” and “dairy farmers” community; (b) the need for capital support or procurement of production means for dairy farming, and (c) the need for increased motivation of the people to develop USPSMWL.